Pengaruh Budaya Organisasi, Employee Engagement Dan Organizational Citizenship Behavior Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil (DISPENDUKCAPIL) Kota Malang - Laila Dian Maslina; Siti Asiyah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and analyze the influence of organizational culture, employee engagement and organizational citizenship behavior. The sample used in this study was 78 respondents using the saturated sample technique. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and partial hypothesis (Test t). The results of this study indicate that simultaneously the variables of organizational culture, employee engagement and organizational citizenship behavior have a positive and significant effect on the performance of employees of the Malang City Population and Civil Registration Office. Meanwhile, partially (t test) organizational culture variable has a positive and significant effect on employee performance, employee engagement variable has no significant effect on employee performance and organizational citizenship behavior variable has a positive and significant effect on employee performance at the Department of Population and Civil Registration of Malang City. Keywords : Organizational Culture, Employee Engagement, Organizational Citizenship Behavior and Employee Perfomance